Lithium secondary battery and method for manufacturing same

By performing at least three pre-cycling processes during the manufacturing process of the lithium secondary battery, the friction between the electrode assembly and the battery case is increased, and the problems of electrode assembly separation and electrolyte leakage during external impact of the lithium secondary battery are solved, and its impact resistance is significantly improved.

CN119585910APending Publication Date: 2025-03-07LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380054001.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-23
Filing Date
2023-12-21
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

When the lithium secondary batteries are impacted externally, there are problems such as electrode assembly separation and electrolyte leakage, resulting in insufficient impact resistance.

Method used

By performing at least three pre-circulation processes after manufacturing the lithium secondary battery, the friction between the inner surface of the battery case and the electrode assembly is increased to reach at least 21 kgf.

Benefits of technology

The impact resistance of the lithium secondary battery is significantly improved, the separation of the electrode assembly during external impact and the leakage of the electrolyte is suppressed, and the electrolyte does not leak during high acceleration and short-term collision impact tests are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585910A_ABST
    Figure CN119585910A_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a lithium secondary battery and a lithium secondary battery, the method comprising: a first step of manufacturing a cell by disposing an electrode assembly in a battery case and injecting an electrolyte; and a second step of performing at least three pre-cycles on the cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium secondary battery and a method for producing the same, and more preferably to a lithium secondary battery having excellent impact resistance and a method for producing the same. Background Art

[0002] Lithium secondary batteries are generally manufactured by coating a positive electrode collector and a negative electrode collector with an electrode active material slurry to manufacture a positive electrode and a negative electrode, stacking the positive electrode and the negative electrode on both sides of a separator to form an electrode assembly having a predetermined shape, and then housing the electrode assembly in a battery case and injecting an electrolyte into the battery case.

[0003] According to the material of the shell that contains the electrode assembly, the secondary battery is divided into a pouch type and a can type. Among them, the pouch type secondary battery is manufactured by the following method: a flexible bag film stack is pressurized to form a cup portion, the electrode assembly is contained in the cup portion, the electrolyte is injected into the cup portion, and the sealing portion is sealed. The can type secondary battery is manufactured by the following method: the electrode assembly is contained in a can made of a metal material, the electrolyte is injected into the can, the top cover is assembled, and the can is sealed.

[0004] Pouch-type secondary batteries have the advantages of being light in weight, excellent in space utilization, and being able to achieve high energy density by using a stacked electrode assembly, but have the limitation of being easily affected by external impacts compared to can-type secondary batteries. Recently, as the use environment of secondary batteries has become more diverse, there is a demand for excellent safety even in harsh environments, and therefore there is also a demand for improving the impact resistance of lithium secondary batteries. Summary of the invention

[0005] [Technical issues]

[0006] To address the above limitations, one aspect of the present invention provides a lithium secondary battery and a method for manufacturing the same, wherein the friction between the inner surface of the battery case and the electrode assembly is increased to at least 21 kgf by performing a pre-cycling process at least 3 times after manufacturing the battery.

[0007] [Technical solution]

[0008] According to one aspect of the present invention, there is provided a method for manufacturing a lithium secondary battery, the method comprising: a first step of disposing an electrode assembly in a battery case and injecting an electrolyte to manufacture a single cell, and a second step of pre-cycling the single cell at least three times within a voltage range of 2.50 V to 4.35 V.

[0009] In this case, the battery case may include a barrier layer, a base layer formed on one surface of the barrier layer, and a sealant layer formed on the other surface of the barrier layer, and may be a pouch including at least one cup portion recessed in one direction.

[0010] In the first step, the electrolyte may be injected so that the amount of the electrolyte per unit capacity of the secondary battery is 2.0 g / Ah to 2.5 g / Ah, preferably 2.1 g / Ah to 2.4 g / Ah.

[0011] Meanwhile, in the second step, the pre-cycle may be performed in the SOC interval of 0 to 99, preferably 0 to 98.5, at a C-rate of 0.1 C to 1 C, preferably 0.1 C to 0.5 C. Furthermore, a process of activating the single cell may be additionally performed between the first step and the second step.

[0012] According to another aspect of the present invention, a lithium secondary battery is provided, comprising a battery case, and an electrode assembly and an electrolyte contained in the battery case, wherein the friction between the battery case and the electrode assembly is at least 21 kgf, preferably 21 kgf to 31 kgf.

[0013] In this case, the battery case may include a barrier layer, a base layer formed on one surface of the barrier layer, and a sealant layer formed on another surface of the barrier layer, and may be a bag including at least one cup portion recessed in one direction, and the electrode assembly and the electrolyte may be accommodated in the cup portion.

[0014] The lithium secondary battery has excellent impact resistance, and thus when a collision impact test is performed under the conditions of an acceleration of 133.7 G and a holding time of 15.8 ms, the electrolyte leakage of the secondary battery is 0.

[0015] [Beneficial Effects]

[0016] When at least three pre-cycle processes are performed as in the lithium secondary battery manufacturing method of the present invention, the friction between the electrode assembly of the lithium secondary battery and the inner surface of the battery case (for example, the bottom surface of the cup portion) is greater than that of the battery manufactured by the conventional method, thereby inhibiting the separation of the electrode assembly and / or the leakage of the electrolyte during external impact and significantly improving the impact resistance of the lithium secondary battery.

[0017] The lithium secondary battery manufactured by this method has a high friction of at least 21 kgf between the electrode assembly and the inner surface of the battery case, so when a collision impact test is performed under the conditions of an acceleration of 133.7 G and a holding time of 15.8 ms, electrolyte leakage does not occur due to damage to the bag. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 1 is a flowchart showing a method for producing a lithium secondary battery according to an embodiment of the present invention.

[0020] Figure 2It is an exploded perspective view of a lithium secondary battery according to an embodiment of the present invention.

[0021] Figure 3 It is a figure which shows the cross section of the bag of this invention. DETAILED DESCRIPTION

[0022] It should be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it should be further understood that these words or terms should be interpreted as having meanings consistent with their meanings in the relevant technical context and the technical concept of the present invention, based on the principle that the inventor can appropriately define the meanings of words or terms to best interpret the present invention.

[0023] Hereinafter, the present invention will be described in more detail through specific embodiments.

[0024] Due to the recent increase in demand for high-capacity batteries such as batteries for electric vehicles, the rated capacity of single secondary batteries has increased, and thus the weight of electrode assemblies has also increased. However, due to the increased weight of the electrode assembly, the movement of the electrode assembly when subjected to external impacts can damage the battery case or the electrode assembly can pierce the battery case, which becomes more serious. When such damage to the battery case occurs, the electrolyte leaks or the electrode assembly is deformed, resulting in severe limitations in battery performance and safety.

[0025] The inventors conducted repeated studies to resolve this limitation and found that when at least three pre-cycles are performed during the manufacture of the battery, the friction between the electrode assembly and the battery case is significantly increased compared to batteries manufactured by conventional methods, thereby suppressing damage to the bag due to separation of the electrode assembly when subjected to external impact, thereby achieving excellent impact resistance, thereby completing the present invention.

[0026] Specifically, the manufacturing method of the lithium secondary battery of the present invention includes: a first step of placing an electrode assembly in a battery housing and injecting an electrolyte to manufacture a single cell, and a second step of pre-cycling the single cell at least 3 times, preferably 3 to 7 times. In this case, the pre-cycling can be performed within a voltage range of 2.50V to 4.35V.

[0027] When the friction between the electrode assembly and the inner surface of the battery case in contact with the electrode assembly increases, the separation of the electrode assembly when subjected to external impact is suppressed, and the friction between the electrode assembly and the inner surface of the battery case is greatly affected by the amount of electrolyte present at the interface between the electrode assembly and the battery case. As in the present invention, when at least 3 pre-cycles are performed, the electrolyte present between the electrode assembly and the battery case is absorbed into the electrode assembly through the breathing process of the battery, so that the amount of electrolyte at the interface between the electrode assembly and the battery case is reduced and, therefore, the friction increases. In the case where the amount of electrolyte injected into the battery case is reduced, the friction may also increase, but in the case of using such a method, there is a limitation in the degradation of the life characteristics due to the reduction in the amount of electrolyte available to the single cell. On the contrary, in the case of performing at least 3 pre-cycles as in the present invention, only the amount of electrolyte at the interface between the electrode assembly and the battery case can be reduced without reducing the amount of available electrolyte, so that there will be no limitation in the degradation of the life.

[0028] Figure 1 The method for manufacturing the lithium secondary battery of the present invention is shown. Figure 2 is a perspective view of a pouch-type lithium secondary battery according to one embodiment of the present invention, Figure 3 The cross section of the bag of the present invention is shown. Figures 1 to 3 The present invention will be described in more detail.

[0029] <Method for producing lithium secondary battery>

[0030] First, a method for producing a lithium secondary battery of the present invention will be described.

[0031] Step 1: Manufacturing steps of single cells

[0032] First, an electrode assembly is disposed in a battery case and an electrolyte is injected to manufacture a unit battery (S1).

[0033] In this case, the battery housing may be, for example, a pouch.

[0034] refer to Figure 2 and Figure 3 The bag 100 includes a barrier layer 20, a base layer 10 formed on one surface of the barrier layer 20, and a sealant layer 30 formed on the other surface of the barrier layer 20, and includes at least one cup portion 110 recessed in one direction.

[0035] Specifically, the bag 100 can be manufactured by inserting a flexible bag film stack having a base layer 10, a barrier layer 20 and a sealant layer 30 stacked in sequence into a pressurizing device, and partially pressurizing the bag film stack with a punch to stretch it, thereby forming a cup portion having a concave shape in one direction.

[0036] The base layer 10 is disposed on the outermost layer of the pouch to protect the electrode assembly from external impact and to electrically insulate the electrode assembly.

[0037] The base layer 10 may be made of a polymer material, for example, at least one polymer material selected from the group consisting of polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, acrylic polymers, polyacrylonitrile, polyimide, polyamide, cellulose, aromatic polyamide, nylon, polyester, poly(p-phenylene benzobisoxazole), polyarylate and Teflon.

[0038] The base layer 10 may be a single layer structure or may be a Figure 3 The multi-layer structure in which mutually different polymer films 12 and 14 are stacked is shown. In the case where the base layer 10 has a multi-layer structure, an adhesive layer 16a may be provided between the polymer films.

[0039] Meanwhile, the total thickness of the base layer 10 may be 10 μm to 60 μm, preferably 20 μm to 50 μm, more preferably 30 μm to 50 μm. When the base layer 10 may have a multilayer structure, the thickness is the thickness including the adhesive layer. When the base layer 10 meets these ranges, the durability, insulation and formability are excellent. When the base layer 10 is too thin, the durability may be reduced, and the base layer 10 may be damaged during the molding process, and when the base layer 10 is too thick, the formability may be deteriorated, the total thickness of the bag may increase, and the energy density may be reduced due to the reduction of the battery accommodation space.

[0040] According to one embodiment, the base layer 10 may have a stacked structure of a polyethylene terephthalate (PET) film and a nylon film. In this case, preferably, the nylon film is disposed on the barrier layer 20, that is, disposed on the inner side, and the polyethylene terephthalate film is disposed on the surface of the bag.

[0041] Since polyethylene terephthalate (PET) has excellent durability and electrical insulation, when the PET film is disposed on the surface of the bag, the durability and insulation are excellent. However, since the adhesion between the PET film and the aluminum alloy film constituting the barrier layer 20 is weak and the elongation behavior is different, when the PET film is disposed on the barrier layer 20, peeling between the base layer 10 and the barrier layer 20 may occur during the molding process, and there is a limitation that the moldability is deteriorated due to the uneven elongation of the barrier layer 20. On the contrary, since the nylon film has an elongation behavior similar to that of the aluminum alloy film constituting the barrier layer 20, when the nylon film is disposed between the polyethylene terephthalate and the barrier layer 20, the effect of improving the moldability can be obtained.

[0042] The thickness of the polyethylene terephthalate film may be 5 μm to 20 μm, preferably 5 μm to 15 μm, more preferably 7 μm to 15 μm, and the thickness of the nylon film may be 10 μm to 40 μm, preferably 10 μm to 35 μm, more preferably 15 μm to 25 μm. When the thickness of the polyethylene terephthalate film and the thickness of the nylon film satisfy the above ranges, respectively, the moldability and rigidity after molding are excellent.

[0043] The barrier layer 20 ensures the mechanical strength of the pouch 100 , blocks the ingress and egress of gas or moisture outside the secondary battery, and prevents leakage of the electrolyte.

[0044] The thickness of the barrier layer 20 may be 40 μm to 100 μm, preferably 50 μm to 80 μm, and more preferably 60 μm to 80 μm. When the thickness of the barrier layer 20 satisfies these ranges, the occurrence of cracks and / or pinholes is reduced when the cup forming depth is increased or two cups are formed due to improved formability, and thus resistance to external stress after forming is improved.

[0045] Meanwhile, the barrier layer 20 may be made of a metal material, and specifically may be made of an aluminum alloy thin film.

[0046] The aluminum alloy film may include aluminum and at least one or two selected from metal elements other than aluminum, such as iron (Fe), copper (Cu), chromium (Cr), manganese (Mn), nickel (Ni), magnesium (Mg), silicon (Si), and zinc (Zn).

[0047] Preferably, the iron (Fe) content of the aluminum alloy film may be 1.2 wt % to 1.7 wt %, preferably 1.3 wt % to 1.7 wt %, more preferably 1.3 wt % to 1.45 wt %. When the iron (Fe) content in the aluminum alloy film satisfies these ranges, even if the cup portion is formed deeper, the generation of cracks or pinholes can be minimized.

[0048] The sealant layer 30 seals the bag by thermocompression bonding, and is provided in the innermost layer of the bag film stack 1 .

[0049] Since the sealant layer 30 is the surface in contact with the electrolyte and the electrode assembly after the bag is formed, the sealant layer 30 must have insulation and corrosion resistance, and since the sealant layer 30 must block material transfer between the inside and the outside by completely sealing the inside, the sealant layer 30 must have excellent sealing properties.

[0050] The sealant layer 30 can be made of a polymer material, such as at least one polymer material selected from the group consisting of polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, acrylic polymers, polyacrylonitrile, polyimide, polyamide, cellulose, aromatic polyamide, nylon, polyester, poly(p-phenylene benzobisoxazole), polyarylate and Teflon. Preferably, the sealant layer 30 contains polypropylene, which has excellent mechanical properties (such as tensile strength, stiffness, surface hardness, wear resistance and heat resistance) and excellent chemical properties (such as corrosion resistance).

[0051] More specifically, the sealant layer 30 may include polypropylene, cast polypropylene (CPP), acid-modified polypropylene, polypropylene-butylene-ethylene copolymer, or a combination thereof.

[0052] The sealant layer 30 may be a single-layer structure, or a multi-layer structure including at least two layers made of different polymer materials.

[0053] The total thickness of the sealant layer may be 60 μm to 100 μm, preferably 60 μm to 90 μm, and more preferably 70 μm to 90 μm. When the thickness of the sealant layer is too small, the durability and insulation of the seal may be deteriorated, and when the thickness of the sealant layer is too large, the flexibility may be deteriorated, and since the total thickness of the bag film stack increases, the energy density relative to the volume may be deteriorated.

[0054] Meanwhile, the bag film stack can be manufactured by a method for manufacturing a bag film stack known in the art. For example, the bag film stack can be manufactured by attaching the base layer 10 to the upper surface of the barrier layer 20 by an adhesive, and forming the sealant layer 30 on the lower surface of the barrier layer 20 by coextrusion or an adhesive, but is not limited thereto.

[0055] The bag 100 is manufactured by inserting the bag film stack into a molding device and applying pressure to a partial area of ​​the bag film stack with a punch to form a cup portion. In this case, the pressure may be 0.3 MPa to 1 MPa, preferably 0.3 MPa to 0.8 MPa, and more preferably 0.4 MPa to 0.6 MPa. If the pressure during the molding of the cup portion is too low, wrinkles may be generated due to excessive stretching, and if the pressure is too high, stretching may not be performed well and the molding depth may be too small.

[0056] Meanwhile, the moving speed of the punch may be 20 mm / min to 80 mm / min, preferably 30 mm / min to 70 mm / min, and more preferably 40 mm / min to 60 mm / min. When the pressure during molding is too low or the moving speed of the punch is too high, wrinkles may be generated due to buckling, and when the pressure during molding is too high or the moving speed of the punch is too low, the strength concentrated at the corner of the cup during molding is large, which may increase the generation of pinholes or cracks.

[0057] The bag 100 manufactured by the method includes a lower shell 101 , an upper shell 102 , and a folded portion 130 connecting the lower shell 101 and the upper shell 102 , wherein the lower shell and the upper shell include a cup portion 110 having a concave shape in one direction.

[0058] Specifically, if Figure 2 As shown, the bag 100 may be a single cup form in which the cup portion 110 is formed only in the lower case 101, but is not limited thereto, and the bag 100 may also be a double cup form in which the cup portion 110 is formed on both the lower case and the upper case. When the bag 100 has a double cup form, since after accommodating the electrode assembly and the electrolyte, the upper case is folded so that the cup portion of the upper case and the cup portion of the lower case face each other, the bag 100 having the double cup form can accommodate a thicker electrode assembly than the bag 100 having the single cup form, and thus the bag 100 having the double cup form has the advantage of achieving higher energy density.

[0059] The cup portion 110 has a space for accommodating the electrode assembly 200. Meanwhile, the bag 100 may include a platform 120 surrounding the cup portion 110. The platform 120 refers to an unformed region in the bag film stack, that is, a region other than the cup portion 110. The platform 120 is a portion sealed by thermal bonding during a sealing process after the electrode assembly 200 is accommodated in the cup portion 110 and an electrolyte is injected.

[0060] The cup portion 110 may include a bottom surface and a peripheral surface. The peripheral surface may connect the bottom surface and the platform 120. The peripheral surface may be provided in a plurality, more specifically, in four. The bottom surface may cover one surface of the electrode assembly 200, and the peripheral surface may surround the outer circumference of the electrode assembly 200.

[0061] Meanwhile, the folding portion 130 may connect the lower case 101 and the upper case 102, may accommodate the electrode assembly 200 in the cup portion 110, and may be folded after injecting the electrolyte so that the upper case 102 seals the cup portion 110 of the lower case 101. Since the lower case 101 and the upper case 102 are integrally connected when the folding portion 130 is included, the number of sides to be sealed may be reduced when a sealing process is performed later, thereby having the effect of improving processability.

[0062] The folding portion 130 is formed spaced apart from the cup portion 110, and the distance between the folding portion 130 and the cup portion 110 may be 0.5 mm to 3 mm, preferably 0.5 mm to 2 mm. When the folding portion 130 and the cup portion 110 are formed too close, folding may not be performed smoothly, and when the folding portion 130 and the cup portion 110 are formed too far, the total volume of the secondary battery may increase, thereby reducing the energy density relative to the volume. When the bag 100 has a double cup housing, the folding portion may be formed to meet the distance relative to each cup portion.

[0063] The unit battery may be manufactured by sealing the sealant layer by heating after the electrode assembly 200 is disposed in the cup portion 110 of the pouch and the pouch is folded so that the lower case 101 and the upper case 102 contact each other. In this case, a separate air pocket space may be formed in the platform 120 .

[0064] In this case, the electrode assembly 200 may include a plurality of electrodes and a plurality of separators alternately stacked. The plurality of electrodes may be alternately stacked with separators therebetween, and may include positive and negative electrodes of opposite polarities.

[0065] refer to Figure 2 , the electrode assembly 200 may be provided with a plurality of electrode tabs 230 welded to each other. The plurality of electrode tabs 230 may be respectively connected to the plurality of electrodes 210 and may extend outside the electrode assembly 200 to serve as a path through which electrons may move between the inside and outside of the electrode assembly 200. The plurality of electrode tabs 230 may be provided within the bag 100.

[0066] The electrode tab 230 connected to the positive electrode and the electrode tab 230 connected to the negative electrode may extend in different directions of the electrode assembly 200. However, the embodiments of the present invention are not limited thereto, and the electrode tab 230 connected to the positive electrode and the electrode tab 230 connected to the negative electrode may extend side by side in the same direction.

[0067] Lead 240 for supplying power to the outside of the secondary battery may be connected to the plurality of electrode tabs 230 by spot welding, laser welding, ultrasonic welding, etc. One end of lead 240 may be connected to the plurality of electrode tabs 230 , and the other end of lead 240 may extend outside of pouch 100 .

[0068] The lead 240 may be partially surrounded by the insulating portion 250. For example, the insulating portion 250 may include an insulating tape. The insulating portion 250 may be placed between the platform 120 and the second shell 102 of the first shell 101, and in this state, the platform 120 and the second shell 102 may be thermally welded. In this case, a portion of the platform 120 and the second shell 102 may be thermally welded to the insulating portion 250. Therefore, the insulating portion 250 may prevent the power generated by the electrode assembly 200 from flowing to the bag 100 through the lead 240, and the sealing of the bag 100 may be maintained.

[0069] Meanwhile, according to the present invention, the ratio of the total length W1 to the total width W2 of the electrode assembly 200 may be 3 to 12, preferably 5 to 10. When the ratio of the total length to the total width satisfies this range, the effect of achieving high energy density in a limited space may be obtained. Here, the total length and the total width may respectively represent the maximum extension length of the electrode assembly in the length direction and the width direction on the plane.

[0070] For example, the electrode assembly may have a total length of 400 mm to 600 mm and a total width of 50 mm to 140 mm, preferably a total length of 450 mm to 550 mm and a total width of 60 mm to 130 mm. When the total length and total width of the electrode assembly meet this specific range, the friction force can be additionally increased without increasing the amount of electrolyte. Here, the total length and total width can represent the maximum extension length of the electrode assembly in the length direction and the width direction on the plane, respectively.

[0071] Meanwhile, the weight of the electrode assembly may be 500 g to 1500 g, preferably 550 g to 1450 g, and more preferably 600 g to 1400 g. When the weight of the electrode assembly satisfies this range, high capacity can be achieved, and the friction between the electrode assembly and the inner surface of the battery case is increased, so that the impact resistance becomes excellent.

[0072] At the same time, at least one fixing member that wraps and fixes the electrode assembly in the full width direction may also be included on the outer surface of the electrode assembly. In the case of an electrode assembly having a rectangular shape (for convenience, referred to as a long battery cell) with a full length longer than the full width, a fixing member that wraps and fixes the electrode assembly in the full width direction may be used to maintain the alignment of the components of the electrode assembly 200 (i.e., the positive electrode, the negative electrode, and the separator).

[0073] The fixing member may include a porous structure. When the fixing member includes a porous structure, the electrolyte may pass through the fixing member and impregnate into the electrode assembly, thereby preventing the electrolyte impregnation of the electrode assembly from being deteriorated due to the fixing member. Specifically, the fixing member may be a finishing tape having a porous structure, wherein an adhesive layer is formed on one surface of a polymer material base layer, but is not limited thereto. The polymer material may be, for example, polyethylene terephthalate (PET), polyvinyl chloride (PVC), polyethylene (PE), etc., but is not limited thereto.

[0074] Preferably, in the width direction of the electrode assembly, the width of the fixing member is 10 mm to 50 mm, preferably 20 mm to 40 mm. When the width of the fixing member is too wide, the area of ​​the outer surface of the electrode assembly covered by the fixing member may increase, so that the contact area with the electrolyte may be reduced, the impregnation of the electrolyte may be deteriorated, and the friction between the electrode assembly and the battery housing may be reduced, so that the impact resistance may be deteriorated. At the same time, when the width of the fixing member is too narrow, the fixing effect of the electrode assembly may be deteriorated.

[0075] At the same time, the number of fixing members provided on the outer surface of the electrode assembly may be 2 to 10, preferably 2 to 8, and more preferably 3 to 7. The fixing members may be arranged in left-right symmetrical positions along the entire length direction, and preferably may be arranged at equal intervals from each other. When the fixing members are provided in plurality and arranged in the above manner, the electrode assembly having a long entire length and a long cell structure may be securely fixed.

[0076] At the same time, the contact area between the fixing member and the electrode assembly may be less than 30% of the total surface area of ​​the electrode assembly, preferably less than 25%, and more preferably less than 20%. Specifically, the contact area between the fixing member and the electrode assembly may be 0 to 30%, 1% to 30%, 5% to 30%, 5% to 25%, or 5% to 20% of the total surface area of ​​the electrode assembly.

[0077] The contact area between the fixing member and the electrode assembly can be controlled by controlling the width of the fixing member used or the number of fixing members used. Since the fixing member commonly used is made of a material having a friction coefficient less than the friction coefficient of the diaphragm provided on the outermost surface of the electrode assembly, the friction between the electrode assembly and the battery case may be weakened when the area of ​​the fixing member surrounding the electrode assembly increases. Therefore, when using the fixing member, it is best to keep the contact area between the electrode assembly and the battery case below 30% to suppress the reduction of friction.

[0078] Next, the electrolyte serves to move lithium ions generated by electrochemical reactions of electrodes during charging and discharging of the secondary battery, and may include an organic solvent and a lithium salt.

[0079] Organic solvents can be used without particular limitation, as long as they can be used as a medium through which ions participating in the electrochemical reaction of the battery can be moved. Specifically, as organic solvents, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group, and may include a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; cyclopentane; and the like. Among these solvents, carbonate solvents are preferred, and more preferably a mixture of cyclic carbonate compounds (e.g., ethylene carbonate or propylene carbonate, etc.) and chain carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.) with high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of the battery.

[0080] Lithium salts can be used without particular limitation as long as they are compounds that can provide lithium ions used in lithium secondary batteries. Specifically, as lithium salts, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. can be used. Lithium salts are preferably used in a concentration range of 0.1M to 5.0M, preferably 0.1M to 3.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that excellent electrolyte performance can be obtained, and lithium ions can be effectively moved.

[0081] In addition to the components of the electrolyte, the electrolyte may additionally include additives in order to improve the life characteristics of the battery, suppress the decrease in battery capacity, increase the discharge capacity of the battery, and the like.

[0082] At the same time, the amount of electrolyte injected of the present invention can make the amount of electrolyte per unit capacity of the secondary battery be 2.0g / Ah to 2.5g / Ah, preferably 2.1g / Ah to 2.4g / Ah, more preferably 2.1g / Ah to 2.3g / Ah. The amount of electrolyte per unit capacity refers to the ratio of the injection amount of the secondary electrolyte (unit: g) to the rated capacity (unit: Ah) of the secondary battery. The rated capacity of a secondary battery refers to the capacity generated when a fully charged battery is continuously discharged at 0.33C and reaches the discharge termination voltage. In this case, the full charge voltage (charge termination voltage) and the discharge termination voltage can be appropriately selected according to the type of the secondary battery. For example, when the secondary battery is an NCM battery, the rated capacity can be the discharge capacity when the secondary battery is charged to 4.25V and discharged to 2.5V at 0.33C. Unit capacity refers to 1Ah.

[0083] When the amount of electrolyte per unit capacity satisfies this range, excellent impact resistance can be achieved without reducing the electrochemical characteristics of the secondary battery. When the amount of electrolyte is too small, the battery performance may deteriorate due to insufficient electrolyte when the battery is working, and when the amount of electrolyte is too much, the effect of improving impact resistance is small. At the same time, according to the present invention, the rated capacity of the secondary battery can be 50Ah to 200Ah, preferably 50Ah to 150Ah, and more preferably 60Ah to 140Ah.

[0084] Meanwhile, after manufacturing the unit cells, an activation process ( S2 ) may be performed.

[0085] The activation process is used to activate the single cell to impart electrical characteristics and to stabilize the electrodes and electrolyte, and can be performed by a general activation method known in the art. For example, the activation process can be performed by a method of charging and discharging the single cell, and can include an aging process and / or a degassing process as needed.

[0086] The charge and discharge process is used to impart electrical characteristics to the single cell by charging and discharging, and to form a solid electrolyte interface (SEI) film on the electrode surface, and the charge and discharge conditions can be appropriately controlled according to the positive electrode, negative electrode and electrolyte composition of the single cell. For example, for a battery using lithium-nickel-cobalt-manganese oxide as a positive electrode active material and graphite as a negative electrode active material, charging and discharging can be performed at a voltage range of 2.0V to 4.4V and at 20°C to 60°C.

[0087] Meanwhile, the aging process is used to evenly distribute the injected electrolyte inside the battery cell and to make the injected electrolyte penetrate well into the positive and negative electrodes, and is performed by storing the single battery at a specific temperature and humidity for a specific period of time. For example, the aging process can be performed at 10°C to 70°C for 0 to 72 hours, but is not limited thereto.

[0088] Meanwhile, the execution order and number of the charge-discharge process and the aging process are not particularly limited and can be appropriately controlled as needed. For example, the charge-discharge process and the aging process can each be independently performed at least once, and the aging can be performed before and / or after the charge-discharge process.

[0089] The degassing process is used to remove the gas inside the single cell. When the electrolyte and the electrode react chemically during the aging process and the charge and discharge process, gas is generated. When the gas remains inside the single cell, the electrochemical performance and the like may deteriorate, so it is desirable to discharge the gas inside the single cell. As the degassing process, the general method used in the technical field can be used without limitation, and there is no particular limitation on the degassing process. For example, the degassing process can be performed by a method of forming a gas outlet on a partial area of ​​the bag and then sealing the gas outlet by hot melting or the like and discharging the gas from the decompression chamber, a method of forming a gas bag on a partial area of ​​the bag and then moving the gas into the gas bag by compression, and then cutting and removing the gas bag, etc.

[0090] Second step: Pre-cycle step

[0091] Then, the single cell manufactured by this method is subjected to at least three pre-cycles.

[0092] According to the research of the inventors of the present invention, when at least three pre-cycles are performed, the friction between the electrode assembly and the battery case is significantly increased, and therefore, the impact resistance is significantly improved by suppressing the separation of the electrode assembly when an external impact occurs. When the pre-cycle is performed twice or less, the effect of improving the impact resistance is small due to the small increase in friction. However, when the pre-cycle is performed too many times, the electrochemical characteristics may deteriorate due to the increased consumption of active materials and electrolytes, and the pre-cycle is preferably performed less than 10 times, preferably less than 7 times.

[0093] The pre-cycling may be performed within a voltage range of 2.50 V to 4.35 V. When the pre-cycling is performed outside this range, voltage performance may be degraded due to overcharging or over-discharging.

[0094] Meanwhile, the pre-cycle may be performed within an SOC range of 0 to 100, preferably 0 to 99, more preferably 0 to 98.5, at a C-rate of 0.1 C to 1 C, preferably 0.1 C to 0.5 C. When the current rate in the pre-cycle is too high, the degradation reaction of the battery may be accelerated, thereby deteriorating the battery performance, and when the SOC range is too narrow, the effect of increasing the friction may be small due to insufficient breathing of the battery.

[0095] The lithium secondary battery of the present invention manufactured through at least three pre-cycles exhibits a higher friction force between the electrode assembly and the bottom surface of the cup than that of a conventional battery.

[0096] Specifically, the lithium secondary battery of the present invention may include a battery housing and an electrode assembly and an electrolyte contained in the battery housing, and the friction between the battery housing and the electrode assembly may be at least 21 kgf, preferably 21 kgf to 31 kgf. In this case, the details of the battery housing, the electrode assembly and the electrolyte are the same as above, so the specific description thereof is omitted.

[0097] The friction force between the electrode assembly and the battery case was measured by the following method.

[0098] The friction force between the electrode assembly and the battery case was evaluated as follows: the battery case (pouch) of the secondary battery was partially cut off, the weld between the negative electrode lead and the electrode assembly was cut off, and the positive electrode tab was connected to a universal testing machine (UTM), and then the applied force was measured while pulling at a speed of 100 mm / min.

[0099] As described above, since the lithium secondary battery of the present invention has high friction between the electrode assembly and the inner surface of the battery case, the separation degree of the electrode assembly when subjected to external impact is small, so the damage of the bag is minimized, and the lithium secondary battery has very excellent impact resistance. Specifically, when the collision impact test is performed under the conditions of acceleration of 133.7G and holding time of 15.8ms, the electrolyte leakage of the lithium secondary battery of the present invention can be 0.

[0100] The collision impact test can be performed by the following method: the battery to be measured is installed in the fixture of the drop impact device, the battery is allowed to fall freely from a specific height in the direction of the electrode ear, and then it is determined whether the battery is damaged. In this case, the free fall height is set in consideration of the collision condition to be measured (acceleration x holding time). Specifically, the free fall height can be set by converting the impact energy under the collision condition to be measured into potential energy, and by calculating the height that can have the converted potential energy in consideration of the weight of the battery to be measured. At the same time, whether the battery is damaged can also be evaluated by whether the electrolyte leaks.

[0101] Example

[0102] Example 1

[0103] A bag with nylon / polyethylene terephthalate / aluminum alloy film / polypropylene stacked in sequence and a cup portion formed was prepared. A stacked electrode assembly with a total length of 548 mm and a total width of 99 mm was housed in the cup portion, and an electrolyte was injected in an amount of 2.3 g / Ah per unit capacity, and then sealed to manufacture a single cell. Next, the single cell was charged and discharged in a voltage range of 2.0 V to 4.25 V and a temperature range of 10°C to 70°C, and then a degassing process was performed to activate it.

[0104] Next, a pre-cycle process of charging the activated single cell to 4.25 V at 0.33 C and discharging to 2.5 V at 0.33 C was performed three times within the SOC range of 0 to 100 to manufacture a pouch-type lithium secondary battery.

[0105] Example 2

[0106] A pouch-type lithium secondary battery was manufactured in the same manner as in Example 1, except that the electrolyte was injected in such a manner that the amount of electrolyte per unit capacity was 2.2 g / Ah.

[0107] Comparative Example 1

[0108] A pouch-type lithium secondary battery was manufactured in the same manner as in Example 1, except that the pre-cycling was not performed.

[0109] Comparative Example 2

[0110] A pouch-type lithium secondary battery was manufactured in the same manner as in Example 1, except that one preliminary cycle was performed.

[0111] Comparative Example 3

[0112] A pouch-type lithium secondary battery was manufactured in the same manner as in Example 1, except that two preliminary cycles were performed.

[0113] Experimental Example 1: Friction Test

[0114] The bags of lithium secondary batteries manufactured in Examples 1, 2, and Comparative Examples 1 to 3 were partially cut off, the welding portion between the negative lead and the electrode assembly was cut off, and the positive electrode ear was connected to a universal testing machine (UTM), after which the applied force was measured while pulling at a speed of 100 mm / min, thereby evaluating the friction between the electrode assembly and the inner surface of the battery case (the bottom surface of the cup). In this case, the friction force is the average value of the friction force measured for each of the three secondary batteries manufactured in the embodiments and comparative examples. The results of the determination are shown in Table 1 below.

[0115] Experimental Example 2: Collision Impact Test

[0116] The pouch-type lithium secondary batteries manufactured in Examples 1 and 2 and Comparative Examples 1 to 3 were subjected to a collision impact test under the conditions of an acceleration of 133.7 G and a holding time of 15.8 ms. The measurement results are shown in Table 1 below. The case where no electrolyte leakage and electrode assembly separation occurred was indicated as "pass", and the case where electrolyte leakage and / or electrode assembly separation occurred was indicated as "failure".

[0117] [Table 1]

[0118] Friction force (unit: kgf) Crash impact test results Example 1 23.3 pass Example 2 24.3 pass Comparative Example 1 13.0 fail Comparative Example 2 14.3 fail Comparative Example 3 20.7 fail

[0119] As shown in Table 1, the secondary batteries of Examples 1 and 2 that were pre-cycled at least 3 times showed a large friction force between the electrode assembly and the battery case, thereby showing excellent impact resistance by suppressing the separation of the electrode assembly under external impact. In contrast, the friction force between the electrode assembly and the battery case of the secondary batteries of Comparative Examples 1 to 3 that were not pre-cycled or pre-cycled less than 2 times was lower than that of the battery of the embodiment, resulting in electrolyte leakage during the collision impact test.

Claims

1. A method for manufacturing a lithium secondary battery, the method comprising: The first step of manufacturing a single cell is to place the electrode assembly in a battery case and inject an electrolyte, and The second step of pre-cycling the single cell at least three times within a voltage range of 2.50V to 4.35V.

2. The method of claim 1, wherein: The battery case includes a barrier layer, a base layer formed on one surface of the barrier layer, and a sealant layer formed on the other surface of the barrier layer, and is a bag including at least one cup portion recessed in one direction.

3. The method of claim 1, wherein: In the first step, the electrolyte is injected so that the amount of the electrolyte per unit capacity of the secondary battery is 2.0 g / Ah to 2.5 g / Ah.

4. The method of claim 1, wherein: In the first step, the electrolyte is injected so that the amount of the electrolyte per unit capacity of the secondary battery is 2.1 g / Ah to 2.4 g / Ah.

5. The method of claim 1, wherein: In the second step, the pre-cycle is performed in the SOC interval of 0 to 100 at a C rate of 0.1C to 1C.

6. The method of claim 1, wherein: In the second step, the pre-cycle is performed 3 to 7 times.

7. The method of claim 1, wherein: An activation process is additionally performed between the first step and the second step.

8. A lithium secondary battery comprising a battery case and an electrode assembly and an electrolyte contained in the battery case, in, The friction force between the inner surface of the battery case and the electrode assembly is at least 21 kgf.

9. The lithium secondary battery according to claim 8, wherein: The battery case includes a barrier layer, a base layer formed on one surface of the barrier layer, and a sealant layer formed on the other surface of the barrier layer, and is a bag including at least one cup portion recessed in one direction.

10. The lithium secondary battery according to claim 9, wherein: The friction force between the bottom surface of the cup portion and the electrode assembly is 21 kgf to 31 kgf.

11. The lithium secondary battery according to claim 8, wherein: When a collision impact test was performed under the conditions of an acceleration of 133.7 G and a holding time of 15.8 ms, the electrolyte leakage amount of the secondary battery was 0.

12. The lithium secondary battery according to claim 8, wherein: The ratio of the total length to the total width of the electrode assembly is 3 to 12.

13. The lithium secondary battery according to claim 8, wherein: The electrode assembly has an overall length of 400 mm to 600 mm and an overall width of 50 mm to 140 mm.

14. The lithium secondary battery according to claim 8, wherein: The rated capacity of the lithium secondary battery is 50Ah to 200Ah.